Aluminizing as a method of improvement of Mar-M247 alloy lifetime - Zagula-Yavorska M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Environmentally friendly high temperature high-activity (HTHA) and high temperature low- activity (HTLA) CVD aluminizing processes were realized on the Mar-M247 heat resistant superalloy substrate that is widely used in the hot section of aircraft engines. Additionally, commercial aluminide coatings deposited in the above-the-pack aluminiznig process were analyzed. The aluminizing of the Mar-M247 superalloy by the HTHA, HTLA and above-the-pack processes led to formation of two layers of the coatings. The outer layer of the coatings formed by the above-the-pack process consisted of the β-NiAl phase with precipitates, while the outer layer of coatings formed by the HTHA and HTLA processes consisted of the pure β-NiAl phase. Aluminizing successfully improved the lifetime of Mar-M247 superalloy. Despite the fact that the coatings formed by the above-the-pack process are thicker and have a higher aluminium concentration than the coatings formed by the HTLA aluminizing and process, the lifetime of the coated superalloy was lower. Moreover the oxidation resistance of the coated superalloy in the HTLA aluminizing process was better than that of the coating in the HTHA aluminizing process. The removal of impurities in the HTLA aluminizing process ensured a “pure” outer layer of the coatings. Clean aluminide coatings may create a purer alumina oxide and may prolong its lifetime.